AEZWIN, an interactive multiple-criteria analysis tool for land resources appraisal - Fischer, Günther (International Institute for Applied Systems Analysis,Food and Agriculture Organization for the United Nations, 1999)
The book is divided into two major sections: The first discusses changes in operational techniques rather than changes in technology; the second presents information of relevance to vessel operators who are either considering the construction of a new vessel or overhauling and re-equipping an existing vessel.